Anti-Müllerian Hormone as a Sensitive Marker of Ovarian Function in Young Cancer Survivors - Maryna Krawczuk-Rybak; Elzbieta Leszczynska; Marta Poznanska; Beata Zelazowska-Rutkowska; Jolanta Wysocka (International Journal of Endocrinology)
We evaluated ovarian function by measuring the levels of anti-Müllerian hormone (AMH), estradiol, and gonadotropins in 83 young women treated for cancer during childhood and adolescence, and classified according to post-treatment gonadal toxicity versus 38 healthy females. Results. The mean AMH values were lower in the entire cohort independently of the risk group as compared to the control, whereas FSH was elevated only in the high risk group. The lowest AMH values were noted in patients after bone marrow transplantation (BMT) and those treated for Hodgkin lymphoma (HL). Nineteen patients (22.9%) had elevated FSH. They all had low AMH values. Lowered AMH values (but with normal FSH and LH) were observed in 43 patients (51.8%). There was no effect of age at the time of treatment (before puberty, during or after puberty) on AMH levels. Conclusion. Our results show the utility of AMH measurement as a sensitive marker of a reduced ovarian reserve in young cancer survivors. Patients after BMT and patients treated for HL, independently of age at treatment (prepuberty or puberty), are at the highest risk of gonadal damage and early menopause.